(untitled) (REMUNOM, 2025)
Objective: To estimate the prevalence of motorcycle accidents attended by the Mobile Emergency Care Service (SAMU) in a large city in Minas Gerais, Brazil, characterizing the victims according to sociodemographic variables and accident-related factors. Materials and Methods: This was a descriptive, retrospective study, evaluating all medical records of accidents attended by SAMU in the city of Montes Claros from January to December 2017. Results: A total of 1,958 records were analyzed. Most of the victims were male (69.2%) and aged between 16 and 30 years (49%). Regarding the timing of the accidents, the majority occurred on Saturdays (17%) and during the night shift (43%). Concerning alcohol consumption, 2.5% of the victims had consumed alcohol prior to the accident, and 0.9% had used other types of drugs. Most accidents involved collisions—car/motorcycle, animal/motorcycle, truck/motorcycle, or bicycle/motorcycle (91.5%). The most common injuries were chest pain (15.7%), followed by abrasions (15.3%), neck pain (14.9%), and fractures (12.9%). Notably, 9.4% of the victims presented with traumatic brain injury (TBI). Regarding outcomes, the majority were referred for hospital care (92.6%), 16.4% refused transportation, and 0.6% resulted in death. Conclusion: The number of motorcycle accidents was high during the analyzed period, with a predominance of young male victims and accidents occurring on weekends, particularly at night. Characterizing the victims provides important information to support the development of public policies, allowing for the planning of preventive measures and health promotion strategies tailored to the profile of the victims and the nature of the events.